Electrical performance and degradation analysis of field-aged PV modules in tropical climates: A comparative experimental study - Islam, Md. Imamul; Mohd Shawal, Jadin; Al Mansur, Ahmed; Alharbi, Talal
Performance degradation is a prevalent phenomenon in solar photovoltaic systems globally, with varying aging profiles and effects depending on environmental and climatic conditions. This paper presents an extensive investigation of the electrical performance, aging mechanisms, and degradation analysis of field-aged PV modules under the tropical climate of Malaysia. Utilizing a combination of visual inspection, I-V curve measurement, and thermal imaging techniques, this research provides a comprehensive assessment of the electrical and thermal properties of field-aged PV modules from two locations in Malaysia over extended periods (8 years at UMPSA and 10 years at Pasir Mas). The multi-faceted approach of the study allows for a deeper understanding of the degradation process, offering insights into the causes and effects of higher current and lower voltage in aged modules. The study found the average annual degradation rates at UMPSA were 0.3% for open circuit voltage (Voc), 0.23% for short circuit current (Isc), 0.81% for maximum power (Pmax), and 0.35% for fill factor (FF) and at Pasir Mas, the average annual degradation rates were 1.124% for Voc, −0.166% for Isc, 1.276% for Pmax, and 0.43% for FF. The study also found that monocrystalline silicon (m-Si) panels experienced an average power degradation of 6.48%, while polycrystalline silicon (p-Si) panels showed a higher degradation of 12.76%. However, Thermal imaging revealed significant temperature variations across the modules, with hotspots reaching up to 11.2 °C above cooler areas in UMPSA panels and an even more pronounced 26.1 °C difference in Pasir Mas modules. These temperature disparities highlight the uneven heat distribution and potential performance issues in the panels. This research contributes to the understanding of PV module degradation in tropical climates and aligns with sustainable development, climate change mitigation efforts, and SDG 7 by promoting sustainable energy solutions.